The Effect of Postoperative Pain on Sleep Quality in Patients with Brain Tumor Surgery - Sema Kocasli; Emine Öner Karaveli; Ercan Bal (KHD-Production, 2023)
This descriptive study investigated the effect of postoperative pain on sleep quality in patients who underwent brain tumor surgery in neurosurgical clinics.The study population consisted of all patients who underwent surgery for a brain tumor between April and October 2022 in the neurosurgical units of a university hospital and a city hospital. The sample consisted of 90 volunteers. Data were collected using a patient information form, the Numerical Rating Scale for Pain (NRS), and the Richards-Campbell Sleep Scale (RCSQ). The data were analyzed using the number, percentage, mean, standard deviation, correlation, and regression analysis. Participants had a mean age of 47.36±16.17 years. Half of the participants were men (50%). Less than half of the participants had a primary school degree (44.4%). Most participants were married (82.2%). Less than half of the participants slept ≥8 hours before hospitalization (43.3%). Most participants had no sleep problems (88.9%) and were not on sleeping pills (98.8%). Participants’ pain scores significantly differed by measurement times (ꭓ2=60.715; p=0.000). They had significantly lower mean second- (4.20±2.58) and third-measurement (3.13±2.36) NRS scores than the first-measurement NRS score (5.57±2.83) in the morning. In the morning, they had a significantly lower mean third-measurement NRS score (3.13±2.36) than the second-measurement NRS score (4.20±2.58). There was a weak negative correlation between the mean first-measurement RCSQ score and the first-measurement NRS (morning) and NRS (evening) scores (p<0.05).There is a negative correlation between sleep quality and pain in patients who underwent surgery for a brain tumor